Diversity and Distribution Patterns of Understory Invasive Plant Species in The Cisorog Block, Mount Tilu Nature Reserve - Supriatna, Ateng; Amalia, Risqi; Akbar, Rahmat Mustahiq Taufiq; Efendi, Muhammad (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2026)
Invasive plants can reduce biodiversity, particularly in understory vegetation, by altering ecosystem composition and dynamics. Conservation areas, such as the Mount Tilu Nature Reserve (NR) in Bandung Regency, play a vital role in maintaining ecological balance. One of its blocks, Cisorog Block, consists of open areas directly adjacent to public activities, which support the growth and spread of invasive species. This study aims to analyze the diversity, distribution patterns, and environmental factors influencing invasive understory species in Cisorog Block. Vegetation analysis and principal component analysis were conducted within a 47- hectare area at three sampling points. A total of 39 invasive species from 21 families were identified. Species with the highest Important Value Index (IVI) included Cyrtandra grandis (93.714%) at station 1, Cyperus odoratus (33.927%) at station 2, and Commelina benghalensis (15.353%) at station 3. The invasive evenness index was relatively high (0.65–0.85), while the diversity index was moderate (1.05–2.96). All species exhibited clumped distribution patterns.The environmental factors most strongly associated with invasive species distribution were light intensity and air humidity. These results emphasize the importance of developing management strategies based on environmental factors to control invasive plants and conserve biodiversity in the Mount Tilu Nature Reserve.